Studies of battery electric propulsion systems for short-distance fishing boats and ferries - Liu,Lanjun (2025)
To mitigate greenhouse gas emissions resulting from the combustion of fossil fuels in conventional transportation—including vehicles, ships, and aircraft—a wide range of alternative energy sources have been explored, such as liquefied natural gas (LNG), methanol, liquefied petroleum gas (LPG), biomass, solar energy, hydrogen, fuel cells, and batteries. Among these, battery electric propulsion systems (BEPS) have emerged as a particularly promising option, offering the potential for zero-emission operation and scalability across various transport sectors. This study investigates the modeling, validation, and application potential of Battery Electric Propulsion Systems (BEPS) and their integration with internal combustion engines in marine configurations. A detailed mathematical framework is developed to describe the physical, economic, and emission-related behaviors of both battery- based and ICE-driven systems. The models are validated against literature results and applied to a case study involving a ferry operating in the Faroe Islands. Key focus areas include the impact of time step sensitivity, emission penalties, and charging strategies on system performance and cost. Additionally, the effect of vessel speed on energy demand and lifecycle economics is assessed. The results highlight the trade- offs between electrification levels, cost-effectiveness, and environmental performance, offering insight into potencial full-electric configurations under real-world operating constraints.